2021
DOI: 10.7712/120121.8743.18961
|View full text |Cite
|
Sign up to set email alerts
|

The Tracking of Modal Parameters for a Reinforced Concrete Building During Low-Medium Intensity Earthquakes

Abstract: This paper presents the results of the dynamic monitoring carried out on a school building in central Italy during the seismic sequence following the first main shock of the 2016 Central Italy earthquake. The building is located in the historical centre of Camerino and consists of a reinforced concrete frame structure with masonry infill walls. The school, dating back to the 60s, underwent seismic retrofit in 2013 through the construction of 2 dissipative towers, a recent patented system for seismic protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Based on the above discussion, it can be simply concluded that, in general, the measure of the period elongation can be assumed as a measure of the damage state of the building: the more the elongation, i.e., the higher the Tin/Tel ratio, the higher the damage state attained by the building. Despite many studies have been carried out on this topic ( [1][2][3][4][5][6][7][8][9][10][11][12] among others), an explicit relation between the Damage State (DS) of 3D RC buildings modelled and analyzed as nonlinear multi-degree-of-freedom system and in presence of infill walls and their period elongation has never been derived. Note that this kind of relations may be also useful to assess, by means of ambient vibration tests, the usability of buildings for which the usability judgment after earthquake may be uncertain only based on visual inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above discussion, it can be simply concluded that, in general, the measure of the period elongation can be assumed as a measure of the damage state of the building: the more the elongation, i.e., the higher the Tin/Tel ratio, the higher the damage state attained by the building. Despite many studies have been carried out on this topic ( [1][2][3][4][5][6][7][8][9][10][11][12] among others), an explicit relation between the Damage State (DS) of 3D RC buildings modelled and analyzed as nonlinear multi-degree-of-freedom system and in presence of infill walls and their period elongation has never been derived. Note that this kind of relations may be also useful to assess, by means of ambient vibration tests, the usability of buildings for which the usability judgment after earthquake may be uncertain only based on visual inspection.…”
Section: Introductionmentioning
confidence: 99%